Recent advances in nanomedicines for regulation of macrophages in wound healing - Alireza Joorabloo; Tianqing Liu (Journal of Nanobiotechnology, 2022)
Abstract Macrophages are essential immune cells and play a major role in the immune response as pro-inflammatory or anti-inflammatory agents depending on their plasticity and functions. Infiltration and activation of macrophages are usually involved in wound healing. Herein, we first described macrophage polarization and their critical functions in wound healing process. It is addressed how macrophages collaborate with other immune cells in the wound microenvironment. Targeting macrophages by manipulating or re-educating macrophages in inflammation using nanomedicines is a novel and feasible strategy for wound management. We discussed the design and physicochemical properties of nanomaterials and their functions for macrophages activation and anti-inflammatory signaling during wound therapy. The mechanism of action of the strategies and appropriate examples are also summarized to highlight the pros and cons of those approaches. Finally, the potential of nanomedicines to modulate macrophage polarization for skin regeneration is discussed.